2016
DOI: 10.1159/000445111
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Gait Analysis in Progressive Supranuclear Palsy and Parkinson's Disease

Abstract: Background: Although changes to gait are an important clinical feature of progressive supranuclear palsy (PSP), systematic analyses have not been well examined, especially in comparison to Parkinson's disease (PD). Methods: The characteristics of gait in 20 PSP patients (14 males and 6 females) were evaluated in comparison to 124 PD patients (64 males and 60 females) and 24 controls, that is, healthy age-matched adults (5 males and 19 females). Gait in patients was recorded in a 10-m walking test at a self-sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 30 publications
3
32
1
Order By: Relevance
“…Some studies included and compared several types of disorders: frailty and mild cognitive impairment; Parkinson disease and dementia (Yoneyama et al, 2016); Parkinson disease and peripheral neuropathy (Sejdic et al, 2014); or Parkinson disease and progressive supranuclear palsy (Hatanaka et al, 2016). Most of the other studies aimed at differentiating pathological and healthy participants.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies included and compared several types of disorders: frailty and mild cognitive impairment; Parkinson disease and dementia (Yoneyama et al, 2016); Parkinson disease and peripheral neuropathy (Sejdic et al, 2014); or Parkinson disease and progressive supranuclear palsy (Hatanaka et al, 2016). Most of the other studies aimed at differentiating pathological and healthy participants.…”
Section: Resultsmentioning
confidence: 99%
“…The MIMAMORI-Gait is a portable motion recorder designed for long-term continuous measurement, and has been approved in Japan for clinical assessment of gait disturbance and the amount of movement in patients with various diseases-such as PD, progressive supranuclear palsy, and vascular parkinsonism-and has been confirmed to be useful clinically [12][13][14][15]26]. The present study was carried out to determine the association between the amount of overall movement over the 24 h measured by the MIMAMORI-Gait and motor symptoms of patients with PD assessed at the outpatient clinic by the UPDRS.…”
Section: Discussionmentioning
confidence: 99%
“…We found just two previous studies looking at gait in PSP. One of these used a single IMU in the lumbar region (8), and detected only a difference in vertical displacement during gait between PSP and PD. The other used two sensors, one attached to each foot (19), and identified significant differences in gait speed and cadence.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies using accelerometers (8) have shown many shared gait abnormalities (9) (10-12) including decreases in velocity, step length, cadence, and mean acceleration. Some differences have also been found, including lower vertical displacement and higher acceleration in PSP.…”
Section: Introductionmentioning
confidence: 99%